Polyamide 6/graphene oxide-g-hindered phenol antioxidant nano-composites: Intercalation structure and synergistic thermal oxidative stabilization effect. (1st April 2019) - Li, Ruiguang; Shi, Kaihua; Ye, Lin; Li, Guangxian
Abstract: The hindered phenol antioxidant (HP) was grafted onto graphene oxide (GO) surface, and polyamide 6 (PA6)/GO-HP nano-composite was manufactured via melt processing. More efficient grafting of PA6 molecules onto GO surface was realized by forming hydrogen bonding, and GO was exfoliated and uniformly distributed in matrix. Compared with PA6/HP and PA6/GO, the oxidation induction time, thermal degradation temperature and E a of PA6/GO-HP composite increased significantly, retention of reduced viscosity and tensile strength were improved, revealing GO-HP hybrid was more efficient than HP or GO to resist thermal oxidation degradation of PA6. Such synergistic thermal oxidative stabilization mechanism was further revealed. Highlights: GO-HP hybrid was prepared by grafting hindered phenol antioxidant onto GO surface. PA6/GO-HP nano-composite was manufactured via melt processing. Exfoliated GO with high graft of PA6 uniformly dispersed in PA6 in presence of HP. Synergistic thermal oxidative stabilization effect of GO-HP on PA6 was achieved.